CTLA4 mRNA is downregulated by miR-155 in regulatory T cells, and reduced blood CTLA4 levels are associated with poor prognosis in metastatic melanoma patients - Vaddi, Prasanna Kumar; Osborne, Douglas Grant; Nicklawsky, Andrew; Williams, Nazanin K.; Menon, Dinoop Ravindran; Smith, Derek; Mayer, Jonathan; Reid, Anna; Domenico, Joanne; Nguyen, Giang Huong; Robinson, William A.; Ziman, Melanie; et al. (Frontiers in Immunology, 2023)
Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) is an immune checkpoint expressed in regulatory T (Treg) cells and activated T lymphocytes. Despite its potential as a treatment strategy for melanoma, CTLA-4 inhibition has limited efficacy. Using data from The Cancer Genome Atlas (TCGA) melanoma database and another dataset, we found that decreased CTLA4 mRNA was associated with a poorer prognosis in metastatic melanoma. To investigate further, we measured blood CTLA4 mRNA in 273 whole-blood samples from an Australian cohort and found that it was lower in metastatic melanoma than in healthy controls and associated with worse patient survival. We confirmed these findings using Cox proportional hazards model analysis and another cohort from the US. Fractionated blood analysis revealed that Treg cells were responsible for the downregulated CTLA4 in metastatic melanoma patients. Further analysis of published data also showed downregulated CTLA-4 surface protein expression in Treg cells of metastatic melanoma compared to healthy donors. Mechanistically, we found that secretomes from human metastatic melanoma cells downregulate CTLA4 mRNA at the post-transcriptional level through miR-155 without interfering with FOXP3 mRNA in human Treg cells. Finally, we found that miR-155 is upregulated in Treg cells from metastatic melanoma patients compared to healthy donors. Our study provides new insights into the underlying mechanisms of reduced CTLA4 expression observed in melanoma patients, demonstrating that post-transcriptional silencing of CTLA4 by miRNA-155 in Treg cells may play a critical role. Since CTLA-4 expression is downregulated in non-responder melanoma patients to anti-PD-1 immunotherapy, targeting miRNA-155 or other factors involved in regulating CTLA4 expression in Treg cells without affecting T cells could be a potential strategy to improve the efficacy of immunotherapy in melanoma. Further research is needed to understand the molecular mechanisms regulating CTLA4 expression in Treg cells and identify potential therapeutic targets for enhancing immune-based therapies.